Digitalization, Flexibility, and Supply Chain Resilience: Examining Their Impact on MSME Supply Chain Performance - Budi Rahardjo; Suliyanto Suliyanto; Daryono Daryono (Penerbit Goodwood, 2026)
Purpose: This study aims to examine whether digitalisation mediates the relationship between supply chain resilience and MSME supply chain performance, and whether flexibility moderates this relationship. Research Methodology: A quantitative survey of 97 MSMEs in Magelang City was analysed using PLS-SEM (SmartPLS). Measurement validity and reliability were evaluated using standard criteria, and hypotheses were tested through bootstrapping. Results: The results show that supply chain resilience positively affects supply chain performance. Digitalization does not mediate the relationship between resilience and performance. However, flexibility significantly strengthens the effect of resilience on performance. Conclusions: Supply chain resilience is a key driver of MSME performance, and flexibility enhances its impact. Digitalization, however, does not function as a mediating mechanism in this context. Limitations: The study is limited to 97 MSMEs in one city, which may restrict generalizability. Contributions: This study contributes to the Resource-Based View (RBV) literature by clarifying the roles of resilience, digitalization, and flexibility in MSME supply chains. It also provides practical guidance for MSME managers and policymakers in improving supply chain performance.